Long Term Follow up of CT Angiography in Low to Intermediate Risk Patients of Suspected Acute Coronary Syndrome (ACS) - Rahman, Fahd Ur; Saif, Mohsin; Siddiqiue, Bilal; Safi, Shoaib Iqbal; Abbas, Mutahir; Khan, Sikandar Azam; Aziz, Zohair; Azad, Naseem; Sarfraz, Sana; Anwar, Maida (Pakistan Armed Forces Medical Journal, 2022)
Objective: To assess long term outcomes of CT Angiography in low to intermediate risk patients of suspected ACS and to assess if CT-angiography is a safe modality to discharge patients with clinically non-significant coronary artery disease.Study Design: Descriptive cross-sectional study Place and Duration of Study: Tertiary Cardiac Center in Rawalpindi, from Dec 2021 to Apr, 2022.Methodology: A total of (n=600) patients who presented with ischemic sounding chest pain and suspicion of acute coronary syndrome (ACS) were selected via consecutive sampling technique and were followed up to 5-months. Patients' demographics, CT-Angiography findings and their outcomes were noted on data collection sheet. Data was analyzed by SPSS version-23. Descriptive statistics were run to present categorical data in frequencies and percentages. Chi-square and Fisher Exact Test was applied to find the association between study variables at 95% CI and 5% margin of error (α=5%). Results: Out of (n=600) suspected cases of acute coronary syndrome (ACS), n=352 (58.7%) were males and n=248 (42.3%) were females. As a result of follow-up of the ptaients, cases that represented in emergency department, readmission cases and revascularized cases were (n=10,4, 1;1.7%, 0.7%, & 0.2%) respectively. Frequency of ACS and STEMI patient was 0.0%. Mortality rate was 0.0%. There was significant association of comorbids with CT-angiography findings and the findings with outcome variables (p0.05).Conclusion: In low to intermediate risk patients of suspected ACS, discharge decision from emergency department based on CT-angiography findings is safe and shows excellent long-term outcomes with no major adverse cardiac event (MACE) on long-term follow-up.